2022
DOI: 10.3390/biomedicines10020250
|View full text |Cite
|
Sign up to set email alerts
|

Mitoquinone Helps Combat the Neurological, Cognitive, and Molecular Consequences of Open Head Traumatic Brain Injury at Chronic Time Point

Abstract: Traumatic brain injury (TBI) is a heterogeneous disease in its origin, neuropathology, and prognosis, with no FDA-approved treatments. The pathology of TBI is complicated and not sufficiently understood, which is the reason why more than 30 clinical trials in the past three decades turned out unsuccessful in phase III. The multifaceted pathophysiology of TBI involves a cascade of metabolic and molecular events including inflammation, oxidative stress, excitotoxicity, and mitochondrial dysfunction. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Mitochondrial impairment as well as oxidative damage represent integral parts of the pathophysiological process associated with rmTBI therein. The observed neuroprotective effects of MitoQ are also in line with previous studies that demonstrated the safe profile of MitoQ and its efficacy in alleviating cognitive impairments and motor deficiencies [23,27,45].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mitochondrial impairment as well as oxidative damage represent integral parts of the pathophysiological process associated with rmTBI therein. The observed neuroprotective effects of MitoQ are also in line with previous studies that demonstrated the safe profile of MitoQ and its efficacy in alleviating cognitive impairments and motor deficiencies [23,27,45].…”
Section: Discussionsupporting
confidence: 90%
“…We have recently shown that MitoQ alleviated fine motor function and learning impairments, reduced reactive astrogliosis, microgliosis, dendritic and axonal shearing, and increased the expression of antioxidant enzymes in a mouse model of rmTBI at a chronic time point defined as 30 days post-injury [22]. Moreover, we have shown that MitoQ enhanced neurological and cognitive functions, (2) decreased the activation of astrocytes and microglia, and improved axonal integrity and neuronal cell count in the cortex 30 days post-injury in a mouse model of moderate open head injury [23].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…TPP-Mitoquinone has shown utility and specificity by targeting the client-binding middle domain of TRAP1 [ 117 ]. Mitoquinone has been demonstrated to have protective properties in various animal models of neurological maladies, such as traumatic brain injury [ 131 ], Huntington’s disease [ 132 ], amyotrophic lateral sclerosis (ALS) [ 133 ], and Alzheimer’s disease [ 134 ]. This finding is contradictory to the working model of TRAP1 function, especially considering that TRAP1 downregulation is observed in Alzheimer’s disease patients [ 135 ] and its overexpression is protective against oxidative stress in ALS [ 62 ].…”
Section: Current State Of Trap1 Inhibitor Developmentmentioning
confidence: 99%
“…This review aimed to explore neuroprotective activities of histone deacetylase inhibitors in ischemic stroke. In line with neuroprotection, Haider et al [27] investigated the role of mitoquinone in chronic neuroprotection post-TBI, and found that mitoquinone reduced gliosis, decreased oxidative stress, limited neuroinflamamtion, and improved axonal integrity and neuronal survival in an open-head CCI mouse model of moderate TBI.…”
mentioning
confidence: 99%